An evaluation of the potential factors affecting lifetime reproductive success in salmonids. (29th June 2021) - Koch, Ilana J.; Narum, Shawn R.
Abstract: Lifetime reproductive success (LRS), the number of offspring produced over an organism's lifetime, is a fundamental component of Darwinian fitness. For taxa such as salmonids with multiple species of conservation concern, understanding the factors affecting LRS is critical for the development and implementation of successful conservation management practices. Here, we reviewed the published literature to synthesize factors affecting LRS in salmonids including significant effects of hatchery rearing, life history, and phenotypic variation, and behavioral and spawning interactions. Additionally, we found that LRS is affected by competitive behavior on the spawning grounds, genetic compatibility, local adaptation, and hybridization. Our review of existing literature revealed limitations of LRS studies, and we emphasize the following areas that warrant further attention in future research: (1) expanding the range of studies assessing LRS across different life‐history strategies, specifically accounting for distinct reproductive and migratory phenotypes; (2) broadening the variety of species represented in salmonid fitness studies; (3) constructing multigenerational pedigrees to track long‐term fitness effects; (4) conducting LRS studies that investigate the effects of aquatic stressors, such as anthropogenic effects, pathogens, environmental factors in both freshwater and marine environments, and assessing overall body condition, and (5) utilizing appropriate statistical approaches to determine the factors that explain the greatest variation in fitness and providing information regarding biological significance, power limitations, and potential sources of error in salmonid parentage studies. Overall, this review emphasizes that studies of LRS have profoundly advanced scientific understanding of salmonid fitness, but substantial challenges need to be overcome to assist with long‐term recovery of these keystone species in aquatic ecosystems.